ROCK - MAGNETIC STUDY OF THE GOGO¸-OW-JORDANOW SERPENTINITE UNIT OF THE PALEOZOIC SUDETIC OPHIOLITE (SOUTH POLAND) - KÌdziąko - Hofmokl, Magdalena (Ofioliti, 2001)
The Sudetic ophiolite is composed of several dismembered fragments of obducted rock series formed in a MOR regime. One of them - the Gogo¸ów - Jordanów massif is built of totally serpentinized ultramafic rocks. The oceanic serpentinization and several later episodes of continental alteration took place in hydrothermal regime and at temperatures lower than the hydrothermal ones. The alteration resulted in the formation of several phases of magnetite partly transformed into martite and maghemite. Some fine-grained magnetites underwent single phase low temperature oxidation leading to formation of a thin maghemite coating around a magnetite core which influenced the rock-magnetic characteristics.